OVX836 Heptameric Nucleoprotein Vaccine Generates Lung Tissue-Resident Memory CD8+ T-Cells for Cross-Protection Against Influenza - Del Campo, Judith; Bouley, Julien; Chevandier, Marion; Rousset, Carine; Haller, Marjorie; Indalecio, Alice; Guyon-Gellin, Delphine; Le Vert, Alexandre; Hill, Fergal; Djebali, Sophia; Leverrier, Yann; Marvel, Jacqueline; et al. (Frontiers in Immunology, 2021)
Tissue-resident memory (TRM) CD8+ T-cells play a crucial role in protection against influenza infection but remain difficult to elicit using recombinant protein vaccines. OVX836 is a recombinant protein vaccine, obtained by fusion of the DNA sequence of the influenza A nucleoprotein (NP) to the DNA sequence of the OVX313 heptamerization domain. We previously demonstrated that OVX836 provides broad-spectrum protection against influenza viruses. Here, we show that OVX836 intramuscular (IM) immunization induces higher numbers of NP-specific IFN-producing CD8+ T-cells in the lung, compared to mutant NP (NPm) and wild-type NP (NPwt), which form monomeric and trimeric structures, respectively. OVX836 induces cytotoxic CD8+ T-cells and high frequencies of lung TRM CD8+ T-cells, while inducing solid protection against lethal influenza virus challenges for at least 90 days. Adoptive transfer experiments demonstrated that protection against diverse influenza subtypes is mediated by NP-specific CD8+ T-cells isolated from the lung and spleen following OVX836 vaccination. OVX836 induces a high number of NP-specific lung CD8+ TRM-cells for long-term protection against influenza viruses.